JUSTIFYING ENTERPRISE RESOURCE PLANNING (ERP) INVESTMENT: A CASE STUDY USING TECHNOLOGY, ORGANIZATION, AND ENVIRONMENT (TOE) FRAMEWORK - rahman, arief; Ratnawati, Yeni (Jurnal RAK (Riset Akuntansi Keuangan), 2022)
The purpose of this study is to analyze the implementation of the Enterprise Resource Planning (ERP) system with the Technology, Organization and Environment (TOE) approach. This study contributes by providing empirical evidence as well as testing the TOE approach in the context of ERP implementation. To be able to answer research questions in depth, this research uses qualitative methods. The method used is semi-structured interview. The informants in this study were 31 people with various levels of positions in the company. To test the validity of this research data using source triangulation. The results of the study conclude that there are challenges or obstacles as well as benefits from implementing an ERP system related to organizational technology and the environment. The results of the study are discussed including their implications for the company and the literature.